Kualitas Pelayanan Terhadap Masyarakat Dalam Pengurusan Izin Mendirikan Bangunandi Kabupaten Enrekang - Jamal, Muh; Adys, Abdul Kadir; Yahya, Muhammad (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to find out how the quality of service in providing building permits in Enrekang Regency. This study used descriptive qualitative research. The number of informants as many as 7 people. Data collection techniques were observation, interviews and documentation. The results of the study concluded that the physical evidence aspect had not been effective because there were still shortcomings of employees in providing services, facilities and infrastructure were sometimes disturbed, the reliability aspect was still less effective because sometimes consumers did not understand to take care of the IMB, from the aspect of responsiveness it was not optimal because sometimes consumers wait a long time to be processed. the data, from the aspect of guarantees it had been maximal because employees provided guarantees to consumers, from the aspect of maximum empathy because a sense of empathy or attention to consumers had been carried out by employees. Keywords: Quality, service, permit